Tourist buying intention towards local food: A Systematic Review - Chamoli, Abhay; Verma, Shiv Mohan; Pandey, Devashish; Uniyal, Naveen; Sajwan, Deepika (The journal of contemporary issues in business and government, 2021)
Local food buying is an important phenomenon in the touristic activity. The study is one of the first attempts to identify all kinds of direct and indirect variables that influence consumers local food buying intentionand analyzing theory of planned behaviour as the baseline model for such research. A systematic literature review on 60 different publications is conducted with application of Bibliometrics of tware(VOSviewer) to exhibit local food research network and tourist local food buying intention.Through a comprehensive review of important publications, the key findings provide, a classification of numerous variables along with (TPB) theory of planned behaviour as a baseline framework for analyzing local food buying intention in sync with existing variables. Important implications through this research are for researchers, marketers and decision-makers who are involved in developing and recognizing concerns relevant to the consumption of local food. The study further limits itself for further analysis in different population regions, with some quantitative approach.